2011
DOI: 10.1007/s11130-011-0224-6
|View full text |Cite
|
Sign up to set email alerts
|

Soy-derived Isoflavones Inhibit HeLa Cell Growth by Inducing Apoptosis

Abstract: Isoflavones are among the major bioactive compounds found in a wide variety of plant-derived foods, especially in soybeans and soy-based foods. In this study, the effect of a soy-derived isoflavone mixture (designated as SI-I, containing 71% daidzein, 14.3% genistein and 14.7% glycitein) on HeLa cells and its mechanism were investigated. SI-I in concentration range 5-80 μg/ml significantly reduced the survival rate of HeLa cells by MTT assay, whereas showed no side effect on that of L929 cells. After HeLa cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…Interestingly, GEN was shown to trigger apoptosis via the ER-dependent up-regulation of cathepsin D in multiple breast cancer cell lines [85]. Our analysis suggests that high levels of GEN may induce apoptosis in cardiomyocytes in accordance with previous reports on other cell types treated by GEN [85][86][87][88].…”
Section: Apoptosissupporting
confidence: 91%
“…Interestingly, GEN was shown to trigger apoptosis via the ER-dependent up-regulation of cathepsin D in multiple breast cancer cell lines [85]. Our analysis suggests that high levels of GEN may induce apoptosis in cardiomyocytes in accordance with previous reports on other cell types treated by GEN [85][86][87][88].…”
Section: Apoptosissupporting
confidence: 91%
“…Further, SPs exhibit anticancer activity (Saleem, 2009); however, the underlying mechanisms are yet to be determined. A recent study reported that soyderived isoflavone mixtures induced apoptosis in HeLa cells by disrupting mitochondrial membrane potentials (Xiao et al, 2011). Although a previous study reported the cytotoxic effects of soy-derived compounds on HeLa cells, this study did not investigate the cause of cell death.…”
Section: Discussionmentioning
confidence: 90%
“…MPP + can activate apoptosis cascade reaction, reduce the mitochondrial membrane potential, accelerate tumor necrosis factor (TNF) transcript, and activate caspase-3 to open holes in the mitochondrial membrane, enhancing its permeability, which eventually lead to dopaminergic neuron's apoptosis. So we tentatively put forward that isoflavone and caspase inhibitors can prevent cell death and Isoflavone may play the role similar to caspase inhibitors in protecting and directly suppresses “apoptosis executives” activities, which effectively resist apoptosis's occurring [ 15 ]. So the result may be due to the fact that isoflavone suppressed MPP + -induced apoptosis in PC12 cells.…”
Section: Discussionmentioning
confidence: 99%